Clinical utility of remote platelet function measurement using P-selectin: assessment of aspirin, clopidogrel and prasugrel, and bleeding disorders - Bath, Philip M.W.; May, Jane; Heptinstall, Stan (Taylor & Francis, 2018)
Vascular diseases such as myocardial infarction and ischaemic stroke are associated with increased platelet function whilst the risk of recurrence is reduced by antiplatelet agents such as aspirin, clopidogrel and prasugrel. However, some patients exhibit high platelet reactivity, especially with clopidogrel. Existing platelet function tests may not be ideal in that they can be expensive, are often time-consuming, and measurements must be made near to the patient and within a few hours of blood collection. Platelet activation leads to translocation of P-selectin from alpha-granules to the cell surface. Following activation with arachidonic acid (which is blocked by aspirin) or adenosine diphosphate (inhibited by clopidogrel) and fixation, samples may be stored or posted to a laboratory performing flow cytometric quantification of platelet P-selectin expression. Acute myocardial infarction and ischaemic stroke are associated with high platelet reactivity on clopidogrel in 6-58% of patients when assessed with P-selectin expression, and high reactivity was associated with an increased risk of recurrence after myocardial infarction. Use of P-selectin expression tests may also be of relevance to surgical and veterinary practice, and the diagnosis of mild bleeding disorders. The present review explores this topic in further detail.